Two new records for the mycoflora of Turkey - Kirba?, Sevda (My University, 2003)
Ustilago heufleri Fuckel. a parasitic species on Tulipa aleppensis Boiss., and Anthracoidea subinclusa (Koern.) Bref., on Carex stenophylla Wahlenb. subsp. stenophylloides (V. Krecz.) Egorova, are recorded for the first time from Turkey.
Türkiye Mantar Florasi için iki Yeni Kayit
Keywords: Anthracoidea subinclusa; New record; Ustilago heufleri